AI Writing Assistants: Insights from EMI Higher Education - Silaen, Disa; Fitria, Risa (IKIP Siliwangi, 2025)
One of the requirement of study in an EMI university is the ability to express ideas through academic writing tasks or projects. This explanatory study aims to investigate EMI university students' strategies of using artificial intelligence-based writing assistants for college writing tasks. This mixed-method study combined survey-based instrument and interviews. The survey was distributed online, consisting of 10 likert scale statements, with 1 = strongly disagree and 5 = strongly agree and 5 close-ended questions. This likert-scale statements seek to map students’ use of AI-based writing assistants in stages of writing process while the close-ended questions seek to explain their perceptions of using AI writing assistants. This questionnaire was followed by interviews to several participants, purposively selected based on their responses in the questionnaire. The survey was distributed to 101 university students from 17 study programs at one university that implements EMI. The results revealed that AI tools support EMI students throughout the whole stages of writing processes, but mainly in pre-writing, drafting, and editing stages. Furthermore, students’ positive views over the support and concerns over significant reliance on the use of AI writing assistants are also discussed. Further research could investigate the long-term effects of using these tools on students' academic writing skills and academic performance.